Predictors of Helmet CPAP Failure in COVID-19 Pneumonia: A Prospective, Multicenter, and Observational Cohort Study - Pierachille Santus; Stefano Pini; Francesco Amati; Marina Saad; Marina Gatti; Michele Mondoni; Francesco Tursi; Maurizio Rizzi; Davide Alberto Chiumello; Valter Monzani; Francesco Blasi; Stefano Aliberti; et al. (Canadian Respiratory Journal)
Background. Continuous positive airway pressure (CPAP) can be beneficial in acute respiratory failure (ARF) due to coronavirus (COVID-19) pneumonia, but delaying endotracheal intubation (ETI) in nonresponders may increase mortality. We aimed at investigating the performance of composite respiratory indexes as possible predictors of CPAP failure in ARF due to COVID-19. Methods. This was a multicenter, prospective, observational, and cohort study conducted in the respiratory units of three University hospitals in Milan and in a secondary care hospital in Codogno (Italy), on consecutive adult patients with ARF due to COVID-19 pneumonia that underwent CPAP between March 2020 and March 2021. ETI transfer to the intensive care unit or death is defined CPAP failure. Predictors of CPAP failure were assessed before T0 and 1 hour after T1 CPAP initiation and included mROX index (ratio of PaO2/FiO2 to respiratory rate), alveolar-to-arterial (A-a) O2 gradient, and the HACOR (heart rate, acidosis, consciousness, oxygenation, and respiratory rate) score. Results. Three hundred and fifty four patients (mean age 64 years, 73% males) were included in the study; 136 (38.4%) satisfied criteria for CPAP failure. A-a O2 gradient, mROX, and HACOR scores were worse in patients who failed CPAP, both at T0 and T1 (p<0.001 for all parameters). The HACOR score was associated with CPAP failure (odds ratio—OR—for every unit increase in HACOR = 1.361; 95%CI: 1.103–1.680; p=0.004; AUROC = 0.742; p<0.001). CPAP failure was best predicted by a threshold of 4.50 (sensitivity = 53% and specificity = 87%). Conclusions. The HACOR score may be a reliable and early predictor of CPAP failure in patients treated for ARF in COVID-19 pneumonia.